Acute coronary syndrome due to unprotected left main stenosis as a culprit lesion: the role of the interventional cardiologist and cardiac surgeon - Tajstra, Mateusz; Gąsior, Mariusz; Zembala, Marian; Poloński, Lech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Left main coronary artery stenosis involves a variety of clinical situations, with frequent underestimation of the degree of stenosis, the absence of specific clinical manifestations, difficult decisions and, above all, a very high mortality risk and an unfavourable long-term prognosis. The optimal coronary revascularization strategy in patients with unprotected left main coronary disease (ULMCD) still remains the subject of an on- going debate. There is a paucity of reports on acute coronary syndromes (ACS) caused by ULMCD. The available literature presents mainly case studies or small observational studies and focuses on patients with myocardial infarction caused by ULM occlusion. As a result, the guidelines on coronary revascularization and ACS management in this group of high-risk patients are ambiguous and give recommendations only in the case of concomitant ULMCD.